The Effect Of Non-Transparent Compensation Systems On Employee Motivation And Performance In The F&B Industry At Pt Jakspan Sentra Batam - Bella Rismayani; Anfas . (Jurnal Ekonomi Manajemen dan Bisnis (JEMB), 2025)
The Food & Beverage (F&B) industry relies heavily on the quality and performance of human resources, making the compensation system implemented by a company a crucial factor in maintaining employee motivation and performance. However, non-transparent compensation practices are still prevalent and can create uncertainty and perceptions of unfairness in the workplace. This study aims to analyze the effect of a non-transparent compensation system on employee motivation and performance at PT Jakspan Sentra Batam. The study used a quantitative approach with a causality method, involving 84 respondents selected through simple random sampling. Data were collected using a questionnaire and analyzed through simple linear regression. The results showed that non-transparent compensation had a positive effect on employee motivation (r = 0.618; p <0.00) and performance (r = 0.604; p <0.00). This finding confirms that although compensation remains a driver of motivation and performance, low levels of transparency can hinder its effectiveness. Therefore, companies need to increase transparency in the compensation system to promote fairness, build trust, and optimize employee motivation and performance in the long term. When companies provide clear, fair, and consistent compensation information, employees feel more understood and valued, which motivates them to perform better. This transparency has not only psychological but also behavioral impacts, reflected in increased productivity and performance.